Social identity change in people with multiple sclerosis: a social identity approach to the role of the family in identity reconstruction - Barker, Alex (2016)
People with multiple sclerosis (MS) undergo changes to their identity and this might have an effect on mood. The subjective experience of this identity change is currently not well understood. Past research highlights that social groups, established prior to diagnosis, might protect against the harmful effects of identity change. No studies have specifically investigated this and the implications this may have for psychological interventions for mood in people with MS.